2006
DOI: 10.1115/1.2364193
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Entropy Noise in Aero-Engine Combustors

Abstract: Strong evidence is presented that entropy noise is the major source of external noise in aero-engine combustion. Entropy noise is generated in the outlet nozzles of combustors. Low-frequency entropy noise, which was predicted earlier in theory and numerical simulations, was successfully detected in a generic aero-engine combustion chamber. It is shown that entropy noise dominates even in the case of thermo-acoustic resonances. In addition to this, a different noise generating mechanism was discovered that is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…(20), which gives the ratio between acoustic and entropy waves produced by the combustion chamber (case CC), and Eqs. (21), (22), (28), and (29), which give the transmitted and generated waves by a compact nozzle (cases SA and AA. For this approach, the expression of is 1…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(20), which gives the ratio between acoustic and entropy waves produced by the combustion chamber (case CC), and Eqs. (21), (22), (28), and (29), which give the transmitted and generated waves by a compact nozzle (cases SA and AA. For this approach, the expression of is 1…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Bake et al [21][22][23][24] worked on the subject, but the separation of direct and indirect combustion noise in a real case is still difficult to evaluate. On one hand, entropy fluctuations are controlled by complicated aerodynamical, thermal, and chemical phenomena.…”
Section: Leykomentioning
confidence: 98%
See 1 more Smart Citation
“…The method revealed delay times from the internal combustor sensor to the far-field microphone, even though the correlated signal contained both periodic and random components. In addition, indirect combustion noise has been investigated numerically and with model-scale experiments by Schemel et al [32], Richter et al [33], and Bake et al [34][35][36].…”
mentioning
confidence: 98%
“…Miles et al (2010) has developed an experiment method to identify the indirect combustion noise and direct combustion noise into different frequency domain using aligned and unaligned coherence techniques. Bake et al (2007;2008; has also demonstrated the indirect combustion noise by using a electrically heated flow as a inlet flow for a convergent-divergent nozzle tube. A numerical simulation of this simple experimental setup was performed by Leykoa et al (2009)…”
Section: Introductionmentioning
confidence: 99%